Representation of Women: A Corpus-based Analysis of Pakistani English Newspapers - Asghar, Salma; Akhter, Urooj (Journal of Communication and Cultural Trends, 2022)
This study investigates the use of gendered lexical items and collocates to deconstruct the patriarchal social system of Pakistan with the help of corpus tools. Media frame the mind and thinking of people with its repetitive announcements. Women being a part of the society are also part of media news but they are underreported by reporters and editors as most of the news are male- filtered news. Pakistani English newspapers are one of the popular sources of getting information across Pakistan. The local social system and male dominating mindset have influenced all types of media in Pakistan. It is observed that like all other fields of life, women are marginalized in Pakistani English newspapers too. It is hypothesized that male are over represented as compared to female and women related news are written by female writers and reporters. A corpus of 270 Pakistani English Newspapers has been selected from The News International, The Dawn and Daily Times with 90 articles from each paper. A corpus-based analysis has been carried out to identify gender discrimination and gender stereotypes in Pakistani society. All collocate of women and men are kept in attention in this work. The results reveal that women are represented as a minority and marginalized victims by male dominating society. On the contrary, the modern writers raise their voices to support and highlight the role of women in society. The study is the first attempt of its kind for an amalgam of corpus-based and CDA approaches. Keywords: representation, corpus-driven analysis, newspapers, women, marginalized, minority